2019
DOI: 10.3991/ijet.v14i02.8718
|View full text |Cite
|
Sign up to set email alerts
|

The Different Roles of Help-Seeking Personalities in Social Support Group Activity on E-Portfolio for Career Development

Abstract: Social Support plays a crucial role between recipients and service providers. It is a strong contributor in reducing the level of uncertainty in a situation, in both relationships with one’s own self, as well as relationships on other levels. It can also be used within a group activity system such as E-Portfolio development. One example of this being the support provided to learners who have reflected on their own experience during a period of transition. However, it is possible that some of the learners who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…This was confirmed in research by Ring, Waugaman and Brackett [38] in which students who had used an ePortfolio were able to more effectively convey their achievements in a mock job interview. Additionally, Wetcho and Na-Songkhla [39] assert that the ePortfolio is a useful tool for building self-efficacy regarding career decisions. They claim that it can help students to make better decisions about their education and professional careers.…”
mentioning
confidence: 99%
“…This was confirmed in research by Ring, Waugaman and Brackett [38] in which students who had used an ePortfolio were able to more effectively convey their achievements in a mock job interview. Additionally, Wetcho and Na-Songkhla [39] assert that the ePortfolio is a useful tool for building self-efficacy regarding career decisions. They claim that it can help students to make better decisions about their education and professional careers.…”
mentioning
confidence: 99%
“…In short, an integrative learning experience with ePortfolio can be achieved either with a single course or across an entire program as long as it is supported by a sustained, thoughtful, and coordinated ePortfolio integration. As noted by education scholars, practitioners, reflection is the key component of any successful integrative ePortfolio learning experience [6,9,10,16,26,27,28,29,30,31,32]. Meaningful and powerful reflections enhance personal development through change in attitude and behavior, which in and of itself can be considered a high-impact behavior [6,9,10,33].…”
Section: Eportfolio As Integrative Social Pedagogy and Reflective Practicementioning
confidence: 99%
“…There is evidence that students getting ready to enter the workforce benefit from the process of making their career ePortfolio. The reflection necessary to develop an ePortfolio can help students make better educational and career-related decisions [24]. Likewise, by organizing their skills and achievements into an ePortfolio the students not only have digital artefacts of their learning, but also formulate how to explain or present their qualifications to a prospective employer [26].…”
Section: 2mentioning
confidence: 99%
“…Furthermore, a study on ePortfolio use among students who took business communication courses, revealed that the ePortfolio fosters self-awareness and active learning, as well as professional identity [17]. Moreover, several researchers identified skills and competences that can be developed through ePortfolios such as goal setting, collaborative learning, autonomous learning, self-assessment skills, reflective skills, digital literacy, digital identity, work readiness, professional identity, selfmanagement, and lifelong learning [18][19][20][21][22][23][24]. Other potential benefits of the ePortfolios for students are: "enhanced learning experiences and outcomes; enhanced employability; enhanced career development; enhanced professional identity and judgement making" (Ref.…”
Section: Introductionmentioning
confidence: 99%